Development of a quantitative method for the analysis of cocaine analogue impregnated into textiles by Raman spectroscopy. Issue 4 (9th November 2017) - Xiao, Linda; Alder, Rhiannon; Mehta, Megha; Krayem, Nadine; Cavasinni, Bianca; Laracy, Sean; Cameron, Shane; Fu, Shanlin
Abstract: Cocaine trafficking in the form of textile impregnation is routinely encountered as a concealment method. Raman spectroscopy has been a popular and successful testing method used for in situ screening of cocaine in textiles and other matrices. Quantitative analysis of cocaine in these matrices using Raman spectroscopy has not been reported to date. This study aimed to develop a simple Raman method for quantifying cocaine using atropine as the model analogue in various types of textiles. Textiles were impregnated with solutions of atropine in methanol. The impregnated atropine was extracted using less hazardous acidified water with the addition of potassium thiocyanate (KSCN) as an internal standard for Raman analysis. Despite the presence of background matrix signals arising from the textiles, the cocaine analogue could easily be identified by its characteristic Raman bands. The successful use of KSCN normalised the analyte signal response due to different textile matrix background interferences and thus removed the need for a matrix‐matched calibration. The method was linear over a concentration range of 6.25–37.5 mg/cm 2 with a coefficient of determination (R 2 ) at 0.975 and acceptable precision and accuracy. A simple and accurate Raman spectroscopy method for the analysis and quantification of a cocaine analogue impregnated in textiles has been developed and validated for the first time. This proof‐of‐concept study has demonstrated that atropine can act as an ideal model compound to study the problem of cocaine impregnation in textile. The method has the potential to be further developed and implemented in real world forensic cases. Abstract : Cocaine analogue impregnated into a variety of textiles can be extracted with dilute acidified water (0.5 M sulfuric acid) and quantitatively measured by using Raman spectroscopy.The use of internal standard potassium thiocyanate (KSCN) in the method removes the need for textile matrix matched calibration.